Abstracts of the Research Hands on PIANO: International Conference on Music Performance - Benetti, Alfonso (2018)
‘Hands on’ PIANO is a meeting dedicated to the piano. It is a unique event due to the symbiosis between two types of meetings: the convention type, of an artistic nature, focusing on a specific musical instrument, and the traditional type of academic research conference, but focusing on a specific instrumental area. ‘Hands on’ PIANO aims to bridge the gap between artistic production and academic research, creating opportunities to combine artists’ and researchers’ knowledge, for mutual benefit.